P-021 TREVO Stent-Retriever Acute Stroke (TRACK) Post-marketing Registry: Interim Revascularization and Clinical Outcome Results Compared to TREVO-2 and NASA Registry. (26th July 2014) - Zaidat, O; Castonguay, A; Veznedaroglu, E; Binning, M; Alshekhlee, A; Abraham, M; Mehta, S; El Khoury, R; Majjhoo, A; Lin, E; Kabbani, M; Froehler, M; et al.
Abstract : Background: Although industry sponsored trials for newer mechanical thrombectomy devices for treatment of acute ischemic stroke (AIS) are promising, limited post-marketing data exist on the use of the TREVO device in every day clinical practice. Objective: The ongoing TREVO Stent-Retriever Acute Stroke (TRACK) Registry aimed to assess the real-world safety, angiographic, and clinical efficacy of the TREVO device in comparison to the results from the TREVO-2 clinical trial and post-marketing North American SOLITAIRE Stent-Retriever Acute (NASA) Stroke Registry. Design/methods: The TRACK Registry recruited clinical sites within the USA. Demographic, clinical, angiographic, and outcome data on patients treated with the TREVO device were collected. Symptomatic intracranial haemorrhage (sICH) was defined as any parenchymal hematoma, SAH, or IVH associated with a worsening of the NIHSS score by ≥4 within 24 h. The primary outcome was achieving TICI ≥2a revascularization. Secondary outcomes were mRS at 3 months, mortality, and sICH. Results: 12 centers contributed data on 93 patients for this interim analysis. Baseline demographics were: women 61.3% (57/93), white 78.5% (73/93), mean age 64.9 ± 17.8 years, median baseline NIHSS of 17 (IQR 14–22), mean fluoroscopic time 37.5 ± 31.9 min, and a mean procedure time of 101 ± 69.1 min. The TICI ≥ 2a and TICI ≥ 2b revascularization rates were 85.6% (77/90) and 65.6% (59/90), compared to the operator reported TICI ≥ 2a rate of 85% in TREVO-2 and 87.5% in NASA, and TICI ≥ 2b rate of 72.5% in NASA. A good outcome of mRS ≤ 2 was demonstrated in 43.0% (40/93), compared to 40% (TREVO-2) and 42% (NASA). The rate of sICH was 8.4% (7/83), compared to 4% (TREVO-2) and 9.9% NASA. 90-day mortality was 21.5% (20/93) versus 29% in TREVO-2 and 30.2% in NASA. Conclusion: The investigator initiated post marketing TRACK Registry demonstrates that the TREVO stent-retriever performance in clinical practice is comparable to the TREVO-2 trial and post-marketing NASA Registry. Disclosures: O. Zaidat: 1; C; Stryker Neurovascular. A. Castonguay: None. E. Veznedaroglu: None. M. Binning: None. A. Alshekhlee: None. M. Abraham: None. S. Mehta: None. R. El Khoury: None. A. Majjhoo: None. E. Lin: None. M. Kabbani: None. M. Froehler: None. T. Nguyen: None.